Contribution of the cryosphere to runoff in “Chinese water tower” based on environmental isotopes - Zongxing Li; Juan Gui; Qi Feng; Baijuan Zhang; Qiao Cui (Geoscience Frontiers, 2023)
Cryospheric meltwater is an important runoff component and it profoundly influences changes in water resources in the Tibetan Plateau. Significant changes in runoff components occur in the three-river headwater region (TRHR), which is an important part of “Chinese Water Tower” due to climate warming. However, these effects remain unclear owing to the sparse and uneven distribution of monitoring sites and limited field investigations. Quantifying the contribution of cryospheric meltwater to outlet runoff is a key scientific question that needs to be addressed. In this study, we analyzed 907 precipitation, river water, ground ice, supra-permafrost water, and glacier snow meltwater samples collected from October 2019 to September 2020 in the TRHR. The following results were obtained: (1) There was significant spatio-temporal variation in stable isotopes in different waters; (2) The seasonal trends of stable isotopes for different waters, the relationship between each water body and the local meteoric water line (LWML) confirmed that river water was mainly recharged by precipitation, supra-permafrost water, and glacier snow meltwater; (3) Precipitation, supra-permafrost water, and glacier snow meltwater accounted for 52%, 39%, and 9% of river water, respectively, during the ablation period according to the end-member mixing analysis (EMMA); (4) In terms of future runoff components, there will be many challenges due to increasing precipitation and evaporation, decreasing snow cover, glacier retreat, and permafrost degradation. Therefore, it is crucial to establish the “star-machine-ground” observation networks, forecast extreme precipitation and hydrological events, build the “TRHE on the Cloud” platform, and implement systematic hydraulic engineering projects to support the management and utilization of water resources in the TRHR. The findings of environmental isotope analysis provide insights into water resources as well as scientific basis for rational use of water resources in the TRHR.